JENIS DAN BAHAN DASAR TEMPAT PERKEMBANGBIAKAN VEKTOR DEMAM BERDARAH DENGUE (DBD) DI KABUPATEN BANJARNEGARA - Nova Pramestuti; Ulfah Farida Trisnawati (BALABA: JURNAL LITBANG PENGENDALIAN PENYAKIT BERSUMBER BINATANG BANJARNEGARA, 2013)
ABSTRACT. Dengue Hemorrhagic Fever (DHF) is a disease caused by the Dengue virus and transmitted by the bite of Aedes sp. In 2009-2010 in the District Banjarnegara dengue cases increased. In 2009-2010, in Banjarnegara district which reported increased of DHF cases. Research objectives were to obtain information on water reservoirs (TPA) as a breeding Ae. aegypti and Ae. albopictus by type and basic materials, landfill as a breeding Ae. aegypti and Ae. Dengue virus positive albopictus species and basic materials. The objective of this study was to get information about containers (TPA) as a breeding places of Ae. aegypti and Ae. albopictus and which Dengue virus infection based on their types and main material. The study was conducted in Kuta Banjarnegara and Parakan Canggah sub district, Wanadadi, Klampok, Singamerta dan Tapen village Banjarnegara district in May to Agust 2012. Larval survey were done around 100 meters of DHF cases with local transmission. Bath, buckets, and refrigerator tray were breeding place type of Ae. aegypti which more founded. Indoor container and used goods were breeding place of Ae. aegypti infected with Dengue virus. Buckets, old tires, used goods and leaf midrib were breeding place of Ae. albopictus which more founded. Refrigerator tray was breeding place of Ae. albopictus infected with Dengue virus. Most of the breeding place Ae. aegypti were made of plastics, ceramics, and cement. Breeding place of Ae. aegypti infected with Dengue virus were made of plastic, ceramic, glass, and rubber . Breeding place of Ae. albopictus and infected with Dengue virus were made of plastic